A Developmental Perspective to Attention-Deficit Hyperactivity Disorder (ADHD) in Children - Emmanuel Afolabi Olusegun (East European Journal of Psycholinguistics, 2016)
The debate about diagnoses and treatment of attention deficit hyperactive disorder (ADHD) in children continue to range on between the developmental and biological perspectives. While there is increasing evidence that support the biological susceptibility of the disorder, a number of researches also emphasized the significant effect of environment on the syndrome. This study used developmental perspectives to evaluate and bring together various bio-psychosocial factors that impact on children diagnosed with ADHD. The study explored and integrated the existing and advancing study on ADHD to a more refined pattern that embraced developmental perspectives. The study also discussed how the linkage in childhood ADHD fits within the developmental psychopathology perspective. The study revealed that ADHD as a developmental disorder is influenced by prenatal, biological and psychosocial environmental risk factors, and suggested that better understanding of genomic susceptibilities, family environment and parental characteristics would transform the pathway for development of ADHD in children.ReferencesAmerican Psychiatric Association.(2000). Diagnostic and StatisticalManual of MentalDisorders. 4th ed. Washington, DC: American Psychiatric Association.American Psychiatric Association.(2013). Diagnostic and StatisticalManual of MentalDisorders.5th ed. Washington, DC: American Psychiatric Association.Arnsten, A.F, (2007). Catecholamine and second messenger influenceson prefrontalcortical networks of “representational knowledge”:a rational bridge between genetics andthe symptoms of mental illness. Cerebral Cortex, 17, i6–i15.Arnsten, A.F, & Pliszka, S.R. (2011). Catecholamine influences on prefrontalcorticalfunction: relevance to treatment of attentiondeficit/hyperactivity disorder and relateddisorders. Pharmacology, Biochemistry and Behavior, 99, 211–216.Atladóttir H.O, Parner E.T, & Schendel D. (2007). Variation in incidence ofneurodevelopmental disorders with season of birth. Epidemiology, 18, 240–245.Barkley, R. A. (2006). Attention deficit/hyperactivity disorder: A handbook for diagnosisand treatment (3rd ed.). New York: GuilfordBaumeister A.A, Hawkins M.F (2001). Incoherence of neuroimaging studies of attentiondeficit/ hyperactivity disorder. Clinical Neuropharmacology, 24, 2–10.Berger I. (2011). Diagnosis of attention deficit hyperactivity disorder: much ado aboutsomething. Israeli Medical Association Journal, 13, 571–574.Berger, A., Posner, M. I. (2000). Pathologies of brain attentionalnetworks. Neuroscienceand Biobehavioral Reviews, 24, 3–5.Biederman J, Faraone S.V, Keenan K, Knee D, &Tsuang M.T (1990): Familygenetic andpsychosocial risk factors in DSM-III attention deficit disorder. Journal of AmericanAcademy of Child and Adolescent Psychiatry, 29, 526 –533.Biederman J, Faraone SV, Keenan K, Tsuang MT (1991b): Evidence of familialassociationbetween attention deficit disorder and major affective disorders. Archives of GeneralPsychiatry, 48, 633–642.Biederman, J, Faraone, S.V, Keenan K, Benjamin, J, Krifcher, B. &Moore C. et al (1992).Further evidence for family-genetic risk factors in attention deficit hyperactivity disorder.Patterns of comorbidity in probands and relativesin psychiatrically and pediatricallyreferred samples. Archives of General Psychiatry, 49, 728 –738.Biederman, J., Milberger, S., Faraone, S. V., Kiely, K., Guite, J.,Mick, E., Ablon, S.,Warburton, R., & Reed, E. (1995). Family environment risk factors for attention deficithyperactivity disorder: A test of Rutter’s indicators of adversity. Archives of GeneralPsychiatry, 52, 464–470.Biederman, J., Faraone, S.V., Mick, E., Spencer,T.,Wilens,T., Kiely,K., Guite, J., Ablon, J.S., Reed, E., & Warburton, R. (1995). High risk for attention deficit hyperactivity disorderamong children of parents with childhood onset of the disorder: A pilot study. Journal ofAmerican Psychiatry, 152, 431–435.Biederman J, Faraone S.V, Monuteaux M, Spencer T, Wilens T, Bober M, et al (2004).Gender effects of attention deficit hyperactivity disorder inadults, revisited. BiologicalPsychiatry, 55, 692–700.Brookes, K.,Mill, J.,&Guindalini,C., et al (2006). Acommon haplotype of the dopaminetransporter geneassociated with attention-deficit/hyperactivity disorderand interactingwithmaternal use of alcohol duringpregnancy. Archives of General Psychiatry, 63, 74–81.Brophy, K., Hawi, Z., Kirley, A., Fitzgerald, M., & Gill, M. (2002). Synaptosomalassociated protein 25 (SNAP-25) and attention deficit hyperactivity disorder (ADHD):Evidence of linkage and association in the Irish population. Molecular Psychiatry, 7 , 913–917Campbell, S. B. (2000). Attention-Deficit/Hyperactivity Disorder: A developmental view.In: Handbook of Developmental Psychopathology. (pp. 383–401). A. J. Sameroff, M.Lewis, & S. Miller (Eds.). New York: Kluwer Academic/Plenum.Carlson, E. A., Jacobvitz, D., & Sroufe, L. A. (1995). A developmental investigation ofinattentiveness and hyperactivity. Child Development, 66, 37–54.Childress, A.C, Berry, S.A (2012). Pharmacotherapy of attention-deficit hyperactivitydisorder in adolescents. Drugs, 72, 309–325.Cortese, S (2012). The neurobiology and genetics of attention-deficit/hyperactivitydisorder (ADHD): what every clinician shouldknow. European Journal of PaediatricNeurology, 16, 422–433.Dopheide, J.A (2005). ASHP therapeutic position statement on theappropriate use ofmedications in the treatment of attention deficit/hyperactivity disorder in paediatricpatients. American Journal of Health System Pharmacy, 62, 1502– 1509.Coghill, D., Nigg, J., Rothenberger, A., Sonuga-Barke, E., & Tannock, R. (2005). Withercausal models in the neuroscience of ADHD? Developmental Science, 8, 105–114.Cummings, E. M., Davies, P., & Campbell, S. B. (2000). Developmental Psychopathologyand Family Process: Research, Theory, and Clinical Implications. New York: Guilford.Faraone, S. V., Perlis, R. H., Doyle, A. E., Smoller, J. W., Goralnick, J. J., Holmgren, M.A., et al. (2005). Molecular genetics of attention-defi cit/hyperactivity disorder. BiologicalPsychiatry, 57 , 1313–1323.Faraone, S, Biederman, J, Krifcher Lehman, B, Keenan, K, Norman, D, Seidman, L. et al.(1993). Evidence for the independent familial transmission of attentiondeficit hyperactivitydisorder and learning disabilities: Results froma family genetic study. American Journalof Psychiatry, 150, 891– 895.Faraone, S. V, Tsuang, M. T. (1995). Methods in psychiatric genetics. In: Textbook inPsychiatric Epidemiology, Tohen, M, Tsuang, M., Zahner, G. (Eds). (pp. 81–134). NewYork: John Wiley& Sons.Faraone, S. V. & Biederman, J. (1998). Neurobiology of attentiondeficit hyperactivitydisorder. Biological Psychiatry, 44, 951–958.Faraone S.V, Biederman J, &MonuteauxM.C. (2001a). Attention deficit hyperactivitydisorder with bipolar disorder in girls: Further evidence for a familial subtype? Journal ofAffect Disorders, 64, 19 –26.Haraone S.V, Doyle A.E (2001): The nature and heritability of attentiondeficit/hyperactivity disorder. Child and Adolescent Psychiatric Clinics of North America,10, 299 –316, viii–ix.Faraone, S.V., & Biederman, J. (2000). Nature, nuture, and attentiondeficit hyperactivitydisorder. Developmental Review, 20, 568–581.Faraone S.V, Perlis R.H, Doyle A.E, Smoller J.W, Goralnick J, &Holmgren M.A, et al.(2005). Molecular genetics of attention deficit hyperactivity disorder. BiologicalPsychiatry, 57, 1313–1323.Gray, J. A., Feldon, J., Rawlins, J. N. P., Hemsley, D. R., & Smith, A. D. (1991) Theneuropsychology of schizophrenia. Behavioral and Brain Sciences, 14, 1–84.Gray, J. A. (1982). The neumpsychology of anxiety. New York: Oxford University Press.Halperin, J. M., & Healey, D. M. (2011). The infl uences of environmental enrichment,cognitive enhancement,and physical exercise on brain development: Can we alter thedevelopmental trajectory of ADHD? Neuroscience and Biobehavioral Reviews, 35 , 621–634.Hauschild K.M, Mouridsen S.E, & Nielsen S. (2005). Season of birth inDanish childrenwith language disorder born in the 1958–1976 period. Neuropsychobiology; 51, 93–99.Hudziak J.J, Rudiger L.P, Neale M.C, Heath A.C, & Todd R.D (2000). A twin study ofinattentive,aggressive, and anxious/depressed behaviors. Journal of the American Academyof Child and Adolescent Psychiatry, 39, 469 –476.Kahn, R. S., Khoury, J. & Nichols,W.C., et al (2003). Role of dopamine transportergenotype and maternal prenatal smoking in childhood hyperactive-impulsive,inattentive,and oppositional behaviors. Journal of Pediatrics, 143, 104–110.Kesner R.P, & Churchwell J.C (2011). An analysis of rat prefrontal cortexin mediatingexecutive function. Neurobiology of Learning and Memory, 96, 417–431.Kuntsi, J.,& Stevenson, J. (2000). Hyperactivity in children:Afocuson genetic research andpsychological theories. Clinical Child and Family Psychology Review, 3, 1–24.Langley, K., Rice, F., & van den Bree, M. B., et al (2005). Maternal smoking duringpregnancy as an environmental risk factor for attention deficit hyperactivity disorderbehaviour. A Review. Minerva Pediatrica, 57, 359–371.Manshadi M, Lippmann S, O’Daniel R, & Blackman A (1983): Alcohol abuse andattention deficit disorder. Journal of Clinical Psychiatry, 44, 379 –380Martin N, Scourfield J, McGuffin P (2002).Observer effects and heritability ofchildhoodattention-deficit hyperactivity disorder symptoms. British Journal of Psychiatry, 80, 260 –265.Neale, B. M., Medland, S. E., Ripke, S., Asherson, P., Franke, B., Lesch, K. P., et al.(2010). Meta-analysis of genome-wide association studies of attention-defi cit/hyperactivity disorder. Journal of the American Academy of Child and AdolescentPsychiatry, 49 , 884–897.Nigg J, Nikolas M, & Burt S. A(2010). Measured gene-by-environment interaction inrelation to attention-deficit/hyperactivity disorder. Journal of the American Academy ofChild and Adolescent Psychiatry, 49, 863–73.Oades, R. D., Lasky-Su, J., Christiansen, H., Faraone, S.V., Sonuga-Barke, E. J.,Banaschewski, T., et al. (2008). The influence of serotonin- and other genes onimpulsivebehavioral aggression and cognitive impulsivity in children with attentiondeficit/hyperactivity. A Developmental Perspective on ADHD disorder (ADHD): Findingsfrom a family-based association test (FBAT) analysis. Behavioral and Brain Functions, 4,4–48.Pastor P. N & Reuben C.A. (2008). Diagnosed attention deficit hyperactivity disorder andlearning disability: United States, 2004–2006. Vital Health Statistics, 10, 1–14.Quay, H. C. (1988a). Attention deficit disorder and the behavioral inhibitionsystem: Therelvance of the neuropsychological theory of Jeffrey A. Gray. In: Attention deficitdisorder: Criteria, cognition, intervention (pp. 117–126). L. M. Bloomingdale & J.Sergeant (Eds.). NewYork: Pergamon.Quay, H. C. (1988b). The behavioral reward and inhibition systems inchildhood behaviordisorder. In: Attentiondeficit disorder W; New research in treatment, psychopharnmcology,and attention (pp. 176–186). L. M. Bloomingdale (Ed.). NA: Pergamon.Quay, H. C. (1996, January). Gray'sbehavioral inhibition in ADHD:An update. Paperpresented at the annual meeting of the InternationalSociety for Research in Child andAdolescent Psychopathology, Los Angeles, CA.Rader, R, McCauley L,& Callen, E.C. (2009). Current strategies in thediagnosis andtreatment of childhood attention-deficit/hyperactivity disorder. American FamilyPhysician, 79, 657–665.Robbins, T. W. (2003). Dopamine and cognition. Currpin Neurol,16, (2), S1–S2.Rutter, M, Cox, A, Tupling, C, Berger, M, &Yule, W. (1975). Attainment and adjustmentin two geographical areas. 1—The prevalence of psychiatric disorders. British Journal ofPsychiatry, 126, 493–509.Rutter, M., &Sroufe, L. A. (2000). Developmental psychopathology: Concepts andchallenges. Development and Psychopathology, 12, 265–296.Sergeant, J. (2000). The cognitive-energetic model: An empiricalapproach to attentiondeficit hyperactivity disorder. Neuroscienceand Biobehavioral Reviews, 24, 7–12.Sherman D, McGue M, &Iacono W (1997). Twin concordance for attention deficithyperactivity disorder: A comparison of teachers’ and mothers’reports. American Journalof Psychiatry, 154, 532–535.Sonuga-Barke, E. J., Auerbach, J., Campbell, S. B., Daley, D., & Thompson, M. (2005).Preschool varieties of hyperactive and dysregulated behaviour: Multiple pathways betweenrisk and disorder. Developmental Science, 8 , 141–150.Sonuga-Barke, E. J., Bitsakou, P., & Thompson, M. (2010). Beyond the dual pathwaymodel: Evidence for the dissociation of timing, inhibitory, and delayrelated impairments inattention-defi cit/hyperactivity disorder. Journal of the American Academy of Child andAdolescent Psychiatry, 49 , 345–355.Sonuga-Barke, E. J., & Halperin, J. (2010). Developmental phenotypes and causalpathways in attention deficit/hyperactivity disorder: Potential targets for earlyintervention? Journal of Child Psychology and Psychiatry, 51, 368–398.Sprich-Buckminster S, Biederman J, Milberger S, Faraone S, &Krifcher LehmanB (1993):Are perinatal complications relevant to the manifestation ofADD? Issues of comorbidityand familiality. Journal of American Academy of Child and Adolescent Psychiatry,32,1032–1037Swanson, J. M., Sunohara, G. A., Kennedy, J. L., Regino,R., Fineberg, E.,Wigal, T.,Lerner, M.,Williams, L., LaHoste,G. J.,&Wigal, S. (1998). Association of the dopaminereceptorD4 (DRD4) gene with a refined phenotype of attention deficithyperactivitydisorder (ADHD): A family–based approach.Molecular Psychiatry, 3, 38–41.Taylor, E. (1999). Developmental neuropsychopathology of attentiondeficit and impulsiveness. Development and Psychopathology, 11, 607–628.Thapar, A.,O’Donovan,M., &Owen,M. J. (2005b). The genetics of attention deficithyperactivity disorder. Human Molecular Genetics, 14, 275–282.Thapar, A., Langley, K.,O’Donovan,M. (2006). Refining the attention deficithyperactivity disorderphenotype formolecular genetic studies. Molecular Psychiatry, 11,714–720.Thapar A, Langley K, &Asherson P, (2007). Gene–environment interplay in attentiondeficit hyperactivity disorder and the importance of a developmental perspective. BritishJournal of Psychiatry 190, 1–3.Tochigi M, Okazaki Y, & Kato N, (2004). What causes seasonality of birth inschizophrenia? Neuroscience Res, 48, 1–11Trent S & Davies W. (2012). The influence of sex-linked genetic mechanisms on attentionand impulsivity. Biological Psychology, 89, 1–13.United States, 2003 and 2007 (2010). Increasing prevalence of parent-reported attentiondeficit/hyperactivity disorder among children, MMWR Morb Mortal Wekly Rep, 59, 1439–43.Yehuda, R. (2000). Biology of posttraumatic stress disorder. Journal of ClinicalPsychiatry, 61, 14–21.Zimmer, L (2009). Positron emission tomography neuroimagingfor a better understandingof the biology of ADHD. Neuropharmacology, 57, 601–607.